Whole-genome resequencing reveals collagen-related genes in Kele pigs. - Yu Dan Zhang; Wei Yuan; Huan Bi; Xiao Yang; Yi Yu Zhang; Wei Chen (PLoS ONE)
Objective To verify the accuracy of collagen-specific SNP mutation loci of Kele pigs selected by whole genome resequencing, and to excavate collagen-related genes of Kele pigs, so as to lay a foundation for further molecular selection. Methods Based on whole genome resequencing, candidate genes related to collagen trait of Kele pig were screened for gene annotation. Through KEGG and GO enrichment analysis of differential genes, we selected four genes that may affect collagen trait of collagen pig, namely COL9A1, COL6A5, COL4A3 and COL4A4. Then 14 specific SNP sites were randomly selected from the four genes for sanger sequencing verification, and finally RT-qPCR was used to verify the expression levels of related genes in different tissues of Kele pigs. Results Our sequencing results revealed that 241.04 G of clean data, Q30 reached 93.96% and the average coverage depth was 9.04×. After data analysis, the SNP annotation of Kele pigs identified 4,570 high-impact mutation sites that could result in protein function loss, with SNPs primarily distributed in the intronic and exonic regions. There were 132,256 middle-impact mutation sites and 318,150 low-impact mutation sites that could potentially impact protein properties. Additionally, The INDEL annotation results revealed a total of 17,806 high-impact mutation sites that could potentially result in the loss of protein function. There were 4740 medium-impact mutation sites that have the potential to affect protein properties, as well as 19,298 low-impact mutation sites. Furthermore, there were 14,197,763 mutation sites of modification influence degree in the analysis. In addition, through real-time fluorescence quantitative PCR results, we found that the expression levels of collagen-related genes COL9A1 and COL6A5 in skin tissues were higher than those in other tissues, and the expression levels of COL4A4 and COL4A3 in kidney tissues were higher than those in other tissues. The SNP site verification results showed that the 14 SNP mutation sites randomly selected by us were the same as the SNP mutation sites screened by whole genome resequencing. Conclusion A total of 307 genes related to collagen traits were excavated, including COL9A1, COL6A5, EP300, SOS2 and EPO, etc. It was found that COL9A1 and COL6A5 genes were significantly expressed in the skin tissue of Kele pigs, and COL4A4 and COL4A3 genes were significantly expressed in the kidney tissue of Kele pigs. The mutations of 14 randomly selected loci in the four related genes were consistent with the results of previous whole genome resequencing analysis, indicating that the specific SNP molecular marker information obtained by whole genome resequencing can be used as the basis for analyzing collagen traits of Kele pig. Our results are conducive to further research on collagen trait regulation of Kele pigs and development and utilization of Kele pigs in the future.